A trajetória intelectual de Eudesia Vieira: educação, feminismos e história pátria (1921-1955) - Galvíncio, Amanda Sousa (2019)
This doctoral research has as main objective to understand the intellectual trajectory of the teacher, doctor, historian and poet Eudésia Vieira. The argument of this theory is that Eudésia Vieira represented as a cultural mediator of the feminine and feminist causes in Paraíba, defending the new woman feminine model, reconciling the traditional woman's illustration and of the progressive woman. The temporal cut of this study takes as reference the dates of publication of its two books of Homeland history: points of Brazil from 1921 and the Terras of the Tabajaras 1955. For this purpose, the texts of their authorship were used as sources, such as Articles in newspapers and magazines, autobiography, poetry and Textbooks. In addition to these, biographies, biographical entries and scholarly researches that dealt with his intellectual contribution have been also investigated. The references of historical hermeneutics and feminist studies helped with the methodological elaboration of the research and the interpretation of the selected sources. The categories of intellectuals and gender allowed, in general, to understand how women were inserted in the intellectual spaces of the period and, in particular, how the presence of Eudésia Vieira took place in places still marked by the male figure. Accordingly, the itinerary of formation of the character was searched, identifying the strong presence of the Catholic religion in the education of women of the period and their participation in the networks of sociability of the state, such as the Association of Primary Teachers and the Historical Geographic Institute of Paraíba, which gave her legitimacy to deal with the feminist and educational issues in vogue. Eventually, we sought to understand the generation of contemporary women writers Eudésia Vieira and the themes they shared about: the defense of women's political participation, education as a nation's regeneration, the abolition of slavery and the ideal of peace of Brazilian and Paraiba identities